The Dynamics of Competitive Insurance Markets - Winter, Ralph A. (Journal of Financial Intermediation, 1994)
According to conventional theory, insurance premiums should be informationally efficient predictors of the present value of policy claims and expenses. This paper develops an alternative theory of insurance market dynamics based on two assumptions. First, insured risks are dependent. Under this assumption, insurers′ net worth determines the market capacity since it is necessary to back the contractual promises to pay claims. Second, in raising net worth, external equity is more costly than internal equity. The theory explains the variation in premiums and insurance contracts over the "insurance cycle" and is supported by tests on postwar data. Journal of Economic Literature Classification Numbers: G1, G22.